The World Food Programme’s Contribution to Addressing the Food Crisis in Syria 2021-2023 - Syafira, Nabilah Nurul; Argenti, Gili (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2026)
Syria experienced a severe food crisis during 2021-2023 driven by to multiple overlapping crises; prolonged armed conflict since 2011, economic collapse, the COVID-19 pandemic, and the devasting February 2023 earthquake. This study analyzes the contribution of the World Food Programme (WFP) in addressing Syria’s food crisis during this period. Adopting a qualitative descriptive approach with document analysis techniques and a Neoliberal Institutionalism theoretical framework, this research examines WFP's programmes, operational strategies, and concrete contributions. Findings reveal that WFP reached 5.5 million people in 2023 through emergency food distribution (averaging 1,700 kcal/day), cash-based transfers for 1.5 million beneficiaries and nutrition programmes for 400,000 children and pregnant or lactating women. Despite a 37% funding gap, humanitarian access restrictions, and persistent security threats, WFP demonstrated adaptive capacity in responding to the crisis. This study contributes to understanding the role of international organizations in managing complex food crises in conflict-affected contexts, while also highlighting the structural limitations of donor-dependent assistance systems.